2015
DOI: 10.1007/s11032-015-0346-x
|View full text |Cite
|
Sign up to set email alerts
|

Identification and distribution of VERNALIZATION1 alleles in Chinese barley (Hordeum vulgare) germplasm

Abstract: VERNALIZATION1 (VRN1) is a central regulator of the vernalization requirement, which affects the yield and geographical distribution of Triticeae crops through regulation of the flowering time. The first intron (Intron I) of VRN1 contains putative cis-elements that mediate repression of VRN1 expression. Allelic variations in Intron I are closely associated with increased VRN1 expression in vernalization-responsive accessions in the absence of vernalization. In this study, diagnostic molecular markers were deve… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 57 publications
0
5
0
Order By: Relevance
“…Mutations in VRN-H1 and the loss of strong cold requirements allowed the expansion of cultivated barley to areas where spring types are more suitable (von Bothmer et al 2003 ; Cockram et al 2011 ), although this explanation can be extended to encompass the role of less strict winter types, adapted to fall sowings in areas with warm winters. In fact, several studies have reported ample allelic variation at VRN-H1 and its relation with geographical distribution, in accordance with this hypothesis (Cockram et al 2007a , b ; Saisho et al 2011 ; Zhang et al 2015a , b ; Dondup et al 2016 ; Contreras‐Moreira et al 2019 ). Besides vernalization response, the VRN-H1 region has also been associated with winter survival in the field and frost tolerance (Francia et al 2004 ; Cuesta-Marcos et al 2015 ), with deep implications on the geographical distribution of barley cultivars.…”
Section: Vernalization Responsementioning
confidence: 53%
See 2 more Smart Citations
“…Mutations in VRN-H1 and the loss of strong cold requirements allowed the expansion of cultivated barley to areas where spring types are more suitable (von Bothmer et al 2003 ; Cockram et al 2011 ), although this explanation can be extended to encompass the role of less strict winter types, adapted to fall sowings in areas with warm winters. In fact, several studies have reported ample allelic variation at VRN-H1 and its relation with geographical distribution, in accordance with this hypothesis (Cockram et al 2007a , b ; Saisho et al 2011 ; Zhang et al 2015a , b ; Dondup et al 2016 ; Contreras‐Moreira et al 2019 ). Besides vernalization response, the VRN-H1 region has also been associated with winter survival in the field and frost tolerance (Francia et al 2004 ; Cuesta-Marcos et al 2015 ), with deep implications on the geographical distribution of barley cultivars.…”
Section: Vernalization Responsementioning
confidence: 53%
“…Polymorphisms at this gene are richer in wheat than in barley. Besides deletions in the first intron (Fu et al 2005 ), like in barley, many mutations have been described in other regulatory regions and coding sequence, all associated with increased expression of the gene and accelerated flowering in the absence of vernalization (Yan et al 2003 , 2004a ; Chu et al 2011 ; Li et al 2013 ; Muterko et al 2015 ; Zhang et al 2015a , b ; Kippes et al 2018 ). These mutations give rise to spring dominant alleles, with the VRN-A1 allele showing the strongest effect on flowering time (lack of vernalization requirement), and VRN-B1 and VRN-D1 alleles showing a weaker effect (reduced vernalization requirement) (Trevaskis et al 2003 ).…”
Section: Vernalization Responsementioning
confidence: 99%
See 1 more Smart Citation
“…This was well demonstrated in the presented case study, where unexpected hybrids derived from natural cross pollination events were identified during the 2020 F 4 field trial (Table S3). This MADS-box transcription factor gene, where 10 deletions (0.5 to 8.9 Kb in size) and one insertion (0.7 Kb) facilitate varying degrees of VRN-H1 de-repression and phenological variation in the absence of vernalization (Cockram et al, 2007(Cockram et al, , 2011Fu et al, 2005;Hemming et al, 2009;Szűcs et al, 2007;von Zitzewitz et al, 2005;Zhang et al, 2015). Similarly, two well-documented hotspots within the 14 Kb coding sequence of the DMD gene are heavily concentrated in large INDELs spanning one or more exons that account for approximately two thirds of all reported human DMD diseases (Aartsma-Rus et al, 2016;Iskandar et al, 2019).…”
Section: Demonstrated Utility Of the Lanftc1 Multiplex Pcr Marker In The F 4 Field Trialmentioning
confidence: 99%
“…Similarly, two well-documented hotspots within the 14 Kb coding sequence of the DMD gene are heavily concentrated in large INDELs spanning one or more exons that account for approximately two thirds of all reported human DMD diseases (Aartsma-Rus et al, 2016;Iskandar et al, 2019). In both cases, the original multiplex PCR assays designed to genotype these hotspots have been frequently revised over the years to accommodate new INDELs as they have been discovered (Abbs et al, 1991;Beggs et al, 1990Beggs et al, , 1991Chamberlain et al, 1988Chamberlain et al, , 1990Cockram et al, 2009;Kunkel et al, 1991;Stockley et al, 2006;Zhang et al, 2015). The LanFTc1 multiplex PCR assay could likewise be adapted in future if necessary.…”
Section: Demonstrated Utility Of the Lanftc1 Multiplex Pcr Marker In The F 4 Field Trialmentioning
confidence: 99%